Hedging options - Chen, Nai-fu; Johnson, Herb (Journal of Financial Economics, 1985)
This paper considers the problem of forming a hedge when there are perceived profit opportunities. We show that the option price obeys a modified Black and Scholes equation. Iterative methods yield the appropriate hedge ratio.